2009
DOI: 10.1158/0008-5472.can-08-4418
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde Dehydrogenase 1 Is a Marker for Normal and Malignant Human Colonic Stem Cells (SC) and Tracks SC Overpopulation during Colon Tumorigenesis

Abstract: Although the concept that cancers originate from stem cells (SC) is becoming scientifically accepted, mechanisms by which SC contribute to tumor initiation and progression are largely unknown. For colorectal cancer (CRC), investigation of this problem has been hindered by a paucity of specific markers for identification and isolation of SC from normal and malignant colon. Accordingly, aldehyde dehydrogenase 1 (ALDH1) was investigated as a possible marker for identifying colonic SC and for tracking them during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

46
835
5
6

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 933 publications
(892 citation statements)
references
References 33 publications
46
835
5
6
Order By: Relevance
“…36 -42 Moreover, several studies have described a clinical influence of ALDH1A1-expressing tumor cells in cancers of breast, colon, prostate, and head and neck, as well as in leukemia. 36,39,40,43,44 These findings raise the intriguing question of how ALDH1A1, in charge of activating the prodifferentiation factor RA, is associated with worsened clinical outcome and an undifferentiated phenotype in both healthy and neoplastic tissues. Taking into account possible mechanisms of alternative RA signaling, it could be of great interest to investigate whether stem and progenitor cells are capable of steering self-generated intracellular RA levels.…”
Section: Discussionmentioning
confidence: 99%
“…36 -42 Moreover, several studies have described a clinical influence of ALDH1A1-expressing tumor cells in cancers of breast, colon, prostate, and head and neck, as well as in leukemia. 36,39,40,43,44 These findings raise the intriguing question of how ALDH1A1, in charge of activating the prodifferentiation factor RA, is associated with worsened clinical outcome and an undifferentiated phenotype in both healthy and neoplastic tissues. Taking into account possible mechanisms of alternative RA signaling, it could be of great interest to investigate whether stem and progenitor cells are capable of steering self-generated intracellular RA levels.…”
Section: Discussionmentioning
confidence: 99%
“…ALDH1 activity identifies normal stem cells and tumor-initiating cells (i.e. CSC) in several human malignancies, where it seems to play an important role in drug resistance, cell proliferation, differentiation and response to oxidative stress (52)(53)(54). It is reported that ALDH1 is required for development of the pancreas during mouse embryogenesis, and is associated with tumorigenic pancreatic cancer cells both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The IF and cytofluorimetric or confocal microscopy analyses of a panel of TAAs previously reported as expressed by CRC (e.g., MAGE, NY-ESO-1, Gp100, SVV-1, COA-1, and IL-13Ra2) (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) revealed that all CICs and FBS tumor cells from patients 1076, 1247, 111011 and 14583 were negative for MAGE and Gp100 and expressed low levels (MRFI = 2-4) of NY-ESO-1 and IL-13Ra2 (data not shown). Sox2, Ep-CAM, and CEA, which in addition to their role as markers associated with CICs or CRC-derived CICs (Supplemental Fig.…”
Section: Coa-1 Recognition By Mltc-derived Lymphocytes Stimulated Witmentioning
confidence: 99%